2015
DOI: 10.3892/or.2015.4115
|View full text |Cite
|
Sign up to set email alerts
|

ZGDHu-1 and fludarabine have a synergistic effect on apoptosis of chronic lymphocytic leukemia cells

Abstract: Abstract. Previously, it was demonstrated that the novel proteasome inhibitor N,N'-di-(m-methylphenyi)-3,6-dimethyl-1,4-dihydro-1,2,4,5-tetrazine-1,4-dicarboamide (ZGDHu-1) possesses activity against chronic lymphocytic leukemia (CLL). In the present study, we attempted to assess whether this drug has a synergistic effect with fludarabine on the apoptosis of CLL cells. Annexin V/PI staining, mitochondrial membrane potential (ΔΨm) and reactive oxygen species (ROS) levels were examined by flow cytometry in short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…ZGDHu-1 [N,N ′ -di-(m-methylphenyi)-3,6-dimethyl-1,4-dihydro-1,2,4,5-tetrazine-1,4-dicarboamide] is a proteasome inhibitor and has been reported to exhibit antitumor activity [ 64 , 65 ]. A study has recently been conducted to assess whether this drug has a synergistic effect with fludarabine and mediates apoptosis in CLL cells [ 66 ]. CLL cell-specific apoptosis occurred through the mitochondrial pathway as normal cells remained unaffected.…”
Section: List Of Therapeutic Compounds Targeting Mitochondrial Biomentioning
confidence: 99%
“…ZGDHu-1 [N,N ′ -di-(m-methylphenyi)-3,6-dimethyl-1,4-dihydro-1,2,4,5-tetrazine-1,4-dicarboamide] is a proteasome inhibitor and has been reported to exhibit antitumor activity [ 64 , 65 ]. A study has recently been conducted to assess whether this drug has a synergistic effect with fludarabine and mediates apoptosis in CLL cells [ 66 ]. CLL cell-specific apoptosis occurred through the mitochondrial pathway as normal cells remained unaffected.…”
Section: List Of Therapeutic Compounds Targeting Mitochondrial Biomentioning
confidence: 99%
“…Thus, reducing the toxicity of fludarabine by reducing its dose and the identification of novel candidate drugs are warranted. In our study, it was revealed that ZGDHu-1 and fludarabine had a synergistic effect on the cytotoxicity and apoptosis of CLL cells, and this effect was also dependent on the loss of ΔΨm, PS translocation and ROS accumulation ( 14 ). The combination also significantly induced the cleavage of caspase-3 and significantly decreased anti-apoptotic Bcl-2 expression in CLL cells ( 14 ).…”
Section: Anti-leukemic Activity Of Zgdhu-1mentioning
confidence: 89%
“…Therefore, the combination of ZGDHu-1 and fludarabine may be useful for the maintenance therapy of patients with CLL, as it can sensitize CLL cells to low doses of fludarabine without increasing the risk of long-term side effects on the immune system or other opportunistic infections ( 14 ). However, numerous important questions remain unresolved regarding what type of biomarkers that distinguish lymphoid malignancies will respond to ZGDHu-1 as a monotherapy or combination with other chemotherapy drugs, and whether relapsed or refractory patients with CLL are sensitive to the ZGDHu-1.…”
Section: Anti-leukemic Activity Of Zgdhu-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Antitumor effects include anti-leukemia cells, proliferation and suppression of pancreatic cancer cells. Potential therapeutic effects include promotion of apoptosis of chronic lymphocytic leukemia (CLL) cells for treatment of lung cancer, a synergistic effect on apoptosis of CLL cells with fludarabine, and excellent results in treatment of acute myeloid leukemia (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%